Television as a pedagogical tool in teacher education (Educação e Pesquisa, 2003)
This article takes up an analysis of the first years of implementation of the ''School TV'' program in the state of Santa Catarina (Brazil) to propose thinking about the educational and pedagogical use of information and communication technologies (ICTs). The integration of current communication media into education processes is a necessary and pressing task, since those techniques are already present in all areas of social life. The question no longer is if integration is to be performed or not, since the dissemination of information technologies has challenged the school with a new language, which is present in society - not just at work but also in leisure and culture - but is still absent from school. However, the innovative pedagogical practice employing ICTs faces an important obstacle: teacher education that, to a large extent, still ignores these issues. The ''School TV'' program presents itself as an effective policy to improve and update teacher education. This work aims at understanding and explaining the ways in which the messages of ''School TV'' are used and the reasons behind the persistence of inadequate uses of the medium as a pedagogical tool, both to teachers self-education (distance learning) and as didactic material in their classes. The study also shows that the integration of the televisual medium into the school space, in its double dimension of pedagogical tool and object of study, still faces difficulties, although television is the communication medium most used by teachers and students.